The Correlation Between the Number of Heater and Energy Saving on Plastic Injection Molding - Hastarina, Merisha; Wahyudi, Bayu; Santoso, Budi; Hafizar, M. Alrisyad (International Journal of Science, Technology & Management, 2022)
The number of human populations is increasing as well as daily needs and consequently increased the number of wastes that being produced including plastic waste. Indonesia itself consumed 17 kg/capita per year. Recycling the plastic waste is one of alternatives way to reduce waste, by melting the plastic waste using six heaters from electrical energy source. This research was conducted to obtain number of heaters that will be used in the injection molding process by considering the time consumed for the temperature of 50? - 210? C. The observation is being done by measuring the temperature and power supplied from 3, 4, 5 and 6 heaters and repeated for 3 times experiment. Based on the measurement data that has been carried out, it is found that the highest average power is the injection with six numbers of heaters consumed 956.80 W. The time measurement required to reach optimal temperature, for 3 number of heaters was taking the longest time which is 2842 Seconds. This condition is in line with the average of electrical power consumed to reach the optimal temperature is the using of the heaters 0.350 kWh. Based on three hypotheses that being done, the result shows that the Ha is accepted and there is significant influence between three models that being made.